SPEECH SYNTHESIZER BASED ON THE PROJECT MBROLA - Arkadiusz Rajs; Agnieszka Banaszak-Piechowska; Paweł Drzycimski (Journal of Education, Health and Sport, 2015)
Rajs Arkadiusz, Banaszak-Piechowska Agnieszka, Drzycimski Paweł. Speech synthesizer based on the project MBROLA. Journal of Education, Health and Sport. 2015;5(12):160-164. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35266